Medical marijuana: a public health perspective - Desai, Ushang; Patel, Paras (International Journal of Basic & Clinical Pharmacology, 2017)
Over the few years medical marijuana is growing in the United States. Because of the medical marijuana legislators able to legalized recreational marijuana in the two states in the US. Marijuana has several potential benefits that help in certain disease. The delivery of marijuana is also important because smoking marijuana has severe side effects. Physicians also play important role in medical marijuana, physicians also divided on the use of medical marijuana. Their attitude towards medical marijuana important for the treatment of disease is important for the community. Marijuana is the most commonly used illegal drug in the US and all over world, several risks associated with it. Major concern is medical marijuana increased the use of marijuana and will create the public health problem in the society. There are several medical benefits from the marijuana but require more research to establish the marijuana as a medicine. Control of medical marijuana is also major issue for the law enforcement agencies and challenge for policymakers also in the United States.